Gambaran Depresi Pada Remaja Korban Kekerasan Seksual - kiki berliana; Dwi Purwanti, S.Kp., SST., M.Kes.; Sukesi, A.Per.Pend., S.Kep., Ns., M.Kes; Dr. K.Kasiati, S.Pd., S.Tr Keb., M.Kes (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2021)
Introduction: Sexual violence or rape is sort of violence that is all too common.. Rape victims as adolescents might suffer form a variety of consequences including psychological trauma in the type of depression. Physical symptoms include a lack of self-efficacy, eating and sleeping disorders, anhedonia, and psychological symptoms such as self-weakness, self-control, sensitivity, a sense of worthlessness, lacking in self, and social symptoms can include withdrawal from the environment and emotional distress. The purpose of this literature review is to examine different study findings on the description of depression in adolescents who have been sexually abused. Methods: PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyzes) and the JBI checklist were used to conduct literature review. The phrases were gathered from 7 databases (Semantic Scholar, Wiley, Sage Journals, Proquest, PubMed, Researche Gate, and Elsevier) which yielded 1781 articles of which 36 were chosen to fit the inclusion criteria. Articles are timed for the previous five years. Results: According of 36 articles review, 6 articles describe low self-concept, 5 articles describe emotional dysregulation, 3 article describes a loss of interest (anhedonia),3 article describes disturbed sleep pattern, 2 article describe an eating disorders, 4 articles describes disturbed psycotic problems, and 3 article describes self harm,4 article describes suicide attempt, and 3 article describes antisocial behavior and 3 articles describes psychotic symptomps. as a description of adolescent depression with sexual violence experiences. Conclution: The incidence of low self concept is the most prevalent of the 36 articles. Discussion : Of course, futher study is indeed to examine other aspects of depression among teenagers who have suffered sexual abuse.”